2022
DOI: 10.1021/acsbiomaterials.1c01532
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Engineering Chimeric Antigen Receptor Macrophages and T Cells by Lipid Nanoparticle-Mediated mRNA Delivery

Abstract: Chimeric antigen receptor (CAR)-engineered adoptive cell therapy marks a revolution in cancer treatment based on the highly successful responses to CAR T cell therapy in the treatment of blood cancers. Due to the versatile structure of CARs, this technology can be easily adapted to other immune cell types, including macrophages and NKs, and applied in the treatment of many other cancers. However, high costs and fatal adverse effects represent significant concerns for future development. In vitro transcribed (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 35 publications
(75 reference statements)
0
24
0
Order By: Relevance
“…Reproduced with permission. [ 177 ] Copyright 2022, American Chemical Society. C) CD5‐targeted LNPs achieved in vivo production of CAR‐T cells.…”
Section: Mrna‐based Cancer Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 177 ] Copyright 2022, American Chemical Society. C) CD5‐targeted LNPs achieved in vivo production of CAR‐T cells.…”
Section: Mrna‐based Cancer Therapymentioning
confidence: 99%
“…Similarly, Ye et al successfully generated CAR macrophages (CAR-Ms) and CAR-T cells ex vivo using the mRNA-LNP platform, both of which showed significant toxic effects for B lymphoma (Figure 10B). [177] Due to their ease of handling and comparable or higher efficacy, LNPs offer a more convenient approach to generating mRNA-based CAR cells.…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, also mRNA transfection of T cells by electroporation bears limitations with regard to method-associated cytotoxicity and low transfection efficacy. As an alternative especially lipid NP that complex mRNA and contain helper lipids for stabilization have been tested for ex vivo T cell transfection with mRNA ( 75 78 ) and plasmid DNA ( 79 ). Based on library screening, Billingsley and coworkers identified an ionizable lipid which induced comparable mRNA transfection efficiency at lower cytotoxicity on Jurkat T cells ( 75 ), and subsequently optimized this vector by varying the molar ratios of DOPE, cholesterol and lipid-anchored PEG ( 76 ).…”
Section: Car-t Cell Engineeringmentioning
confidence: 99%
“…The optimized formulation conferred CAR mRNA transfection of primary T cells at similar efficacy as electroporation and viral transfer, yielding comparable CAR-T-mediated target cell killing. By screening a library encompassing chemically differing lipid-like formulations, termed lipidoids, Zhao and coworkers showed that lipidoids with an imidazole group yielded stronger reporter mRNA transfection efficacies of primary human CD8 + T cells in vitro ( 77 ), and was suitable for transfer of CAR-T mRNA into CD8 + T cells as reflected from potent killing activity of lymphoma cells ( 78 ). Furthermore, lipoids also mediated efficient in vivo transfection of T cells as assessed by applying Cre recombinase-encoding mRNA into a reporter mouse strain yielding dTomato expression in response to Cre recombinase-mediated recombination ( 77 ).…”
Section: Car-t Cell Engineeringmentioning
confidence: 99%